Elderly bedridden patients with dementia use over one quarter of resources in internal medicine wards in an Israeli hospital - Inbal Weiss Salz; Yehuda Carmeli; Avi Levin; Noga Fallach; Tali Braun; Sharon Amit (BMC, 2020)
Abstract Background Elderly bedridden patients with dementia (EBRPD) are a growing segment of the population. We aimed to describe acute care hospitalization of EBRPD in internal medicine wards: the prevalence of EBRPD, their impact on hospital resources and hospital ecology, one-year survival, and one-year readmission-free survival. Methods The study setting was the internal medicine division of one tertiary care hospital in Israel. We conducted a point-prevalence survey to measure the prevalence of EBRPD and the prevalence of multidrug-resistant organism (MDRO) carriage. We also conducted a retrospective chart review of EBRPD who were hospitalized in the internal medicine division in order to assess resource use, survival, and readmission. Results In the point prevalence surveys (N = 1667 patients), EBRPD comprised 24.3% of patients and 59.0% of mechanically ventilated patients. EBRPD were twice as likely to be colonized or infected by MDROs as other patients (39.3% vs. 18%, p < 0.001); thus, 41% of MDRO carriers during the survey days were EBRPD. In the retrospective study (N = 517 EBRPD), 80% of EBRPD received antibiotics; on average, they received an antibiotic on 87.7% of their hospital days. One-year survival was 35.6% and one-year readmission-free survival was 16.4%. Conclusions Acute care hospitalization of EBRPD accounted for a high proportion of bed occupancy and ventilator use in internal medicine wards. EBRPD significantly increase the potential for MDRO transmission. Policymakers should seek alternatives to acute care hospitalization for EBRPD.